Layer by Layer Silver Acetate based Coating on Glass and Cement Substrates to Tailor Reflectance and Conductance - Ghusoon M. Ali; Maan S. Hassan; Ehssan S. Hassan; Mohammed O. Dawood (Journal of Engineering and Technological Sciences, 2020)
Tailoring reflectance and conductance was achieved through layer by layer assembly of a silver acetate based multilayer coating. The coating was applied over glass and cement substrates by sol-gel spin coating and by brush painting, respectively. The structural, optical and electrical characteristics and the composition of the coating were studied. The diffraction peaks for all films revealed that the face-centered cubic lattice of the silver crystal structure and the films with more layers had a higher degree of crystallinity. The optical characteristics showed that having more layers leads to decreasing transmittance and increasing reflectance. The I-V characteristics of all samples showed typical ohmic contacts in a voltage range of -1 to 1 V. The conductance increased drastically as the coating developed into multiple layers. The eight-layer coated glass and cement based substrates had very low surface resistance, at 4 â„¦ and 2 â„¦ at 1 V, respectively. The study also revealed that the resistance behavior of a multilayered film generally is thermally stable for annealing up to 400 °C. The coating resistance was significantly increased by further increasing the post-annealing beyond 500 °C. The studied multilayered coating can be used to tailor the reflectance and conductance of dielectric substrate surfaces for various optoelectronics and sensor device applications.